Economic Competitiveness of SMEs: Digital Literacy, The Mediating Role of Digital Transformation and Innovation Capability - Firmansyah, Deri; Ahman, Eeng; Wahdiniwaty, Rahma (Universitas Mercu Buana, 2024)
Objectives: The objective of this study is to predict and analyze the mediating role of digital transformation (DT) innovation capability (IC) and digital literacy (DL) on the relationship between digital literacy (DL) and economic competitiveness (CP) of SMEs, by proposing a model construction.Methodology: The survey method was carried out by distributing research instruments to 99 respondents, the collected data was used to analyze the relationship between digital literacy, digital transformation, innovation ability, and competitiveness, and also used to test hypotheses. Evaluation of predictions through structural equation models with partial least squares-structural equation modeling (PLS-SEM).Finding: DL directly has a significant positive effect on CP. DL has a significant positive influence on DT. DL has a significant positive effect on IC. DT has a significant positive effect on CP. DT has a significant positive effect on IC. DT and IC serially have a mediating effect on the effect of DL on CP, each moderately mediating effect. Conclusion: The results of model measurement and the results of the evaluation of model suitability show that model suitability is achieved and guarantees model suitability. The results of the structural model path analysis show that all hypotheses are accepted, DT and IC serially have a mediating effect on the influence of DL on the economic competitiveness of SMEs. The novelty findings of this research produce a model of the economic competitiveness of SMEs in the digital economy era, which involves DL, DT, and IC. The implication is that to improve the effectiveness of highly competitive businesses in this era, DL, digital competence and digital transformation capabilities of human resources (HRDT) among SMEs need to be carefully prepared, and IC must be improved.